Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Berbantuan Media Kartu Kuartet terhadap Partisipasi Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila Kelas VII di SMPN 11 Mataram - Hermanto Jaelani; M. Ismail; Basariah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of implementing the Make A Match type cooperative learning model assisted by quartet card media on students’ learning participation in the Pancasila Education subject for seventh-grade students at SMPN 11 Mataram. This research employed a quantitative approach with a quasi-experimental design using the Nonequivalent Control Group Design. The population of this study consisted of all seventh-grade students of SMPN 11 Mataram, totaling 98 students. The sample was determined using random sampling techniques, resulting in class VII C as the experimental class and class VII D as the control class, with a total sample of 48 students. Data collection techniques included observation and a student learning participation questionnaire. The research instruments were first tested for validity and reliability. Data analysis was conducted through prerequisite tests, namely normality and homogeneity tests, followed by hypothesis testing using an independent t-test at a 5% significance level. The results of the study indicate that there is a significant effect of implementing the Make A Match type cooperative learning model assisted by quartet card media on students’ learning participation. This is evidenced by the hypothesis testing results showing that the calculated t-value is greater than the t-table value, so the alternative hypothesis is accepted. The implementation of the Make A Match type cooperative learning model assisted by quartet card media was able to increase student engagement, learning interaction, and active participation during the Pancasila Education learning process.